Transforming Method of Torsional Tuned Liquid Column Damper-Eccentric Structure to Torsional Tuned Mass Damper-Eccentric Structure for Vibration Control. Issue 2 (3rd April 2021) - Chuan, Fu
Abstract: The performance of torsional tuned liquid column dampers (TTLCDs) for mitigating coupled lateral and torsional vibrations of an eccentric structure, which can be modeled as a 3 N degree-of-freedom structure, is theoretically investigated. Biaxial horizontal earthquakes are applied at the rigid foundation as a single-point excitation. The equations of relative fluid motion in a TTLCD with different reference points A and inclined angles β of upright columns are derived. Moreover, the interaction forces and moments between the absorber and structure are determined. On the basis of the coupled equations of motion of the main system with the TTLCD, a TTLCD is tuned with respect to a selected natural frequency of the main structure through a geometric transformation in analogy to a torsional tuned mass damper (TTMD). An equivalent structure mass ratio renders the mass of the TTMD and the changed structural modal mass. Thus, the easy implementation of the simulated TTMD by Ansys software can analyze the vibration control of an eccentric structure installed with TTLCDs. Numerical simulations show that a transforming method with an explicit physical definition is feasible and accurate, and can be directly used.